Judicial Discretion in Marriage Dispensation Cases: A Socio-Legal Study at the Bangkinang Religious Court, Kampar-Riau, Indonesia - Padmilah, Padmilah; Husti, Ilyas; Zailani, Zailani; Jamal, Khairunnas (Postgraduate Studies of UIN Sunan Ampel Surabaya, Indonesia, 2026)
The enactment of Law No. 16 of 2019, which raised the minimum marriage age to 19, has paradoxically contributed to a significant increase in marriage dispensation applications in Indonesia. This study examines the exercise of judicial discretion in marriage dispensation cases at the Bangkinang Religious Court and analyzes its socio-legal implications for children and their families. Employing a qualitative socio-legal approach, the research is based on document analysis of four court decisions in 2024 and in-depth interviews with judges, families, and community actors. The findings reveal that judicial discretion is not solely grounded in statutory norms but is substantially shaped by contextual considerations, including moral urgency, psychological readiness, economic capacity, and familial support. However, the frequent granting of dispensations raises critical concerns regarding the erosion of child protection principles and the potential normalization of underage marriage. The study argues for the establishment of clearer regulatory guidelines and a multidisciplinary assessment framework to ensure that judicial discretion aligns with the best interests of the child and broader social justice objectives.